Zastosowanie fizykoterapii w leczeniu dolegliwości bólowych odcinka lędźwiowego kręgosłupa = The use of physical therapy in the treatment of pain lumbar spine - Plaskiewicz, Anna; Kałużny, Krystian; Kochański, Bartosz; Płoszaj, Ola; Lulińska-Kuklik, Ewelina; Weber-Rajek, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Plaskiewicz Anna, Kałużny Krystian, Kochański Bartosz, Płoszaj Ola, Lulińska-Kuklik Ewelina, Weber-Rajek Magdalena, Zukow Walery. Zastosowanie fizykoterapii w leczeniu dolegliwości bólowych odcinka lędźwiowego kręgosłupa = The use of physical therapy in the treatment of pain lumbar spine. Journal of Education, Health and Sport. 2015;5(5):11-20. ISSN 2391-8306. DOI: 10.5281/zenodo.17290 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A11-20 http://dx.doi.org/10.5281/zenodo.17290 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 15.04.2015. Zastosowanie fizykoterapii w leczeniu dolegliwości bólowych odcinka lędźwiowego kręgosłupa The use of physical therapy in the treatment of pain lumbar spine Anna Plaskiewicz1, Krystian Kałużny1, Bartosz Kochański1, Ola Płoszaj2, Ewelina Lulińska-Kuklik2, Magdalena Weber-Rajek3, Walery Zukow4 1) Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2) Bydgoska Szkoła Wyższa, Bydgoszcz 3) Katedra Fizjoterapii, Zakład Kinezyterapii i Masażu Leczniczego, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 4) Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Dolegliwości bólowe kręgosłupa stanowią jeden z największych problemów zdrowotnych współczesnego społeczeństwa. W leczeniu zachowawczym dolegliwości bólowych kręgosłupa stosuje się wiele form i specjalistycznych metod terapii. Jedną z nich jest fizykoterapia. W pracy zaprezentowano zastosowanie oraz rolę fizykoterapii w leczeniu dolegliwości bólowych kręgosłupa w odcinku lędźwiowym. Przedstawiono wybrane formy leczenia fizykalnego tj. termoterapia, elektroterapia, magnetoterapia, laseroterapia oraz ultradźwięki. Opisano działanie poszczególnych bodźców na organizm oraz zwrócono uwagę na wskazania i przeciwwskazania do leczenia fizykalnego. Słowa kluczowe: dolegliwości bólowe kręgosłupa, leczenie zachowawcze, fizykoterapia. Abstract Back pain is one of the major health problems of modern society. The conservative treatment of back pain used many forms and specialized treatments. One of them is physical therapy. The paper presents the application and the role of physical therapy in the treatment of pain in the lumbar spine. The authors present the selected forms of physical treatment, ie. Thermotherapy, electrotherapy, magnetic, laser and ultrasound. This paper describes the effect of various stimuli on the body, and drew attention to the indications and contraindications for physical therapy. Keywords: back pain, conservative treatment, physical therapy.